PERANCANGAN BUKU BATIK TULIS MANGROVE PESISIR RUNGKUT SURABAYA DENGAN TEKNIK FOTOGRAFI GUNA MENINGKATKAN BRAND AWARENESS PADA MASYARAKAT KOTA SURABAYA. - Aisyah, Tito IStnain Nur; Budiardjo, Hardman; Rizky, Muhammad (Jurnal Art Nouveau, 2016)
AbstractIndonesias cultural diversity is very much, so that the community helped preserve the culture in their respective areas so as not to be lost. One of the main owned by Indonesia lies in the city of Surabaya, which has Batik Mangrove is located in Rungkut. Batik Mangrove using a dye made from the processed waste at the Mangrove Forest.By using the benefit book portable media, providing information that is accurate, then the book contains the history, the way of making and telling the whole Batik Mangrove contained therein and given Illustrations image to be more easily recognized and studied by all ages especially the city of Surabaya.On the basis of a view of the above, the researchers are interested in Brand Awareness raised about Batik Mangrove to the citizens of Surabaya through book illustration. Researchers hoped that the book Illustration of Batik Mangrove Surabaya, Surabaya know Batik Mangrove community and also as an inspiration other batik.Creation of book illustration as an attempt was made to preserve the cultural values in Indonesia, as the people of Indonesia, especially in the city of Surabaya with the Batik Mangrove patented become Batik Surabaya. Illustration book is expected to assert that Batik Mangrove can be Brand Batik Surabaya, as well as the effort of learning for the general public.Keyword : Recycling, natural, Mangrove, Illustration, culture.